2006
DOI: 10.7547/0960238
|View full text |Cite
|
Sign up to set email alerts
|

Relative Metatarsal Protrusion in the Adult

Abstract: We performed a bibliographic review of the systems proposed by various researchers to evaluate physiologic metatarsal protrusion. The system of measurement devised by Hardy and Clapham to evaluate the protrusion between the first and second metatarsals was adapted to study the whole metatarsal parabola. We studied the five metatarsals of 52 normal feet. Mean metatarsal protrusion relative to the second metatarsal was +1.21% for the first metatarsal, -3.84% for the third metatarsal, -9.66% for the fourth metata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The data obtained in the present study are also similar to those cited by Hardy and Clapham in 1951 [5], Munuera-Martínez et al in 2004 [29], and Domínguez et al in 2006 [36]. …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The data obtained in the present study are also similar to those cited by Hardy and Clapham in 1951 [5], Munuera-Martínez et al in 2004 [29], and Domínguez et al in 2006 [36]. …”
Section: Resultssupporting
confidence: 92%
“…The latter found a mean value of MTT II–IV relative protrusion of –13.74 mm for men and –10.24 mm for women in the control group, against the –12.33 mm for men and −9.60 mm for women found in the present study. In 2006, the authors [36] found mean values of metatarsal protrusion in a specimen of 52 feet of +1.22% for metatarsal I, −3.84% for metatarsal III, −9.66% for metatarsal IV, and –16.91% for metatarsal V (there were no differences between male and female feet). These mean values are close to data from the current study showing mean values of metatarsal protrusion of +0.94% for metatarsal I, −4.44% for metatarsal III, −11.17% for metatarsal IV, and −20.21% for metatarsal V.…”
Section: Resultsmentioning
confidence: 99%
“…2) falls within a normal range for adults. [15][16][17][18] Despite the experimental nature of this study, one immediate application taken from this research is that future study of MPD and hallux valgus should employ methods that capture the 3-D spatial relationship of the anatomy of the foot.…”
Section: Discussionmentioning
confidence: 99%
“…Though the selection of the proximal point of reference is dependent on method, 14 MPD averages between plus or minus 2 millimeters (mm) in adults. [1][2][3][4][5][6][15][16][17][18] A positive value indicates protrusion of the first metatarsal. 15,19 Metatarsal protrusion distance was measured in this study using a technique called for by LaPorta et al, 16 but with modification to record the relative difference in the actual length of the first and second rays.…”
mentioning
confidence: 99%
“…Several studies have utilised x-ray methodology [4,[7][8][9][10][11] in order to estimate relative metatarsal length. However, this method has many disadvantages due to cost, accessibility and ionising radiation exposure [12,13].…”
Section: Introductionmentioning
confidence: 99%